2021
DOI: 10.1007/s11573-021-01069-2
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and bank risk

Abstract: The concept of sustainable banking has developed significantly in recent years. Previous research found that corporate social responsibility reduces firm risk, yet this empirical evidence refers almost exclusively to non-financial companies and it remains unclear whether the risk-mitigating effect stems from the environmental, social, or governance pillar. The paper aims to analyse the impact of corporate social responsibility activities on bank risk and to explore its determinants. Using a sample of 582 banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…, 2011; John et al. , 2008; Neitzert and Petras, 2022). In this study, we adopted the indexes developed by Wind (the market leader in China's financial information services industry, dedicated to providing accurate and real-time information and sophisticated communication platforms for financial professionals).…”
Section: Methodsmentioning
confidence: 99%
“…, 2011; John et al. , 2008; Neitzert and Petras, 2022). In this study, we adopted the indexes developed by Wind (the market leader in China's financial information services industry, dedicated to providing accurate and real-time information and sophisticated communication platforms for financial professionals).…”
Section: Methodsmentioning
confidence: 99%
“…However, CEOs seem to underestimate risk from a risk management perspective when implementing their banking strategies and policies (Attig, 2021;Jilani and Chouaibi, 2021;Neitzert and Petras, 2022). CEOs are reluctant to employ external financing because of their bias, which causes them to misjudge the value of their bank.…”
Section: 23mentioning
confidence: 99%
“…Stakeholders other than investors may encourage CEOs to reduce risk-taking to a level that is closer to the optimum by exercising their authority to restrict access to resources, whereas stakeholder investment may necessitate a shift toward riskier investments. CEO seems to underestimate the risk from a risk management perspective when implementing their banking strategies and policies (Neitzert and Petras, 2022). Bolton (2013) showed that CSR engagements have a negative impact on bank risk in the financial industry in the USA.…”
Section: 23mentioning
confidence: 99%
“…In Finger et al ( 2018 )’s study of the effect of the equatorial principle on the business performance of banks, the authors note that for banks in developing nations, adhering to the equatorial principle is a long-term strategic decision. In terms of social responsibility (S), the fulfillment of social responsibility can enhance the reputation of banks, assist them in enhancing their asset quality, and reduce the risk effect of banks on an aggregate level (Neitzert and Petras 2022 ; Shen et al 2016 ). In terms of corporate governance (G), research focuses primarily on the influence of executive characteristics on bank performance (Luh Peter et al 2022 ; Saerang et al 2018 ; Skała and Weill 2018 ), commercial bank credit risk management (Chernobai et al 2021 ; Ratnovski 2013 ; Santomero 1997 ), and bank profitability (Abbas et al 2019 ; Omankhanlen et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%